Working smarter from home : your day - your way - Struck, Nancy (Crisp Pub. Menlo Pub.US, 1995)
Discusses topics including: efficient time use and developing systems which make effective organization possible. Advises on facing and fighting counter-productive self-management practices including; snacking, sleeping late; and working too much. Looks at how to manage interruptions; and the need to define and evaluate goals.